Group graded Morita equivalences for wreath products - MINUȚĂ, Virgilius-Aurelian (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
Starting with group graded Morita equivalences, we obtain Morita equivalences for tensor products and wreath products. Mathematics Subject Classification (2010): 16W50, 20E22, 20C05, 20C20, 16D90, 16S35.